Sickle cell disease in Germany: results from a national registry - Kunz, Joachim; Tagliaferri, Laura; Beck, Dorothea; Kulozik, Andreas (Pediatric blood & cancer, 2020)
Background - Limited data on the prevalence and medical care of sickle cell disease (SCD) in Germany are available. Here, we make use of a patient registry to characterize the burden of disease and the treatment modalities for patients with SCD in Germany.